PENGARUH SUPPLY CHAIN MANAGEMENT TERHADAP KINERJA UKM YANG DIMEDIASI OLEH KEUNGGULAN BERSAING - Wardana, Aditya; Kusmantini, Titik (Ekonomi & Bisnis, 2024)
This study aims to determine the effect of supply chain management on SME's performance mediated by competitive advantage. The method in this study uses partial least squares structural equation modeling (PLS-SEM) which is a multivariate data analysis method for complex relationships among constructs and indicators. Researchers used the PLS.3.0 application. The population of this study is SMEs located in Yogyakarta. Determination of the sample using purposive sampling where the SMEs included in the study are SMEs registered in SiBakul and the results obtained as many as 100 research samples. For model feasibility using the Goodness of fit test of 69%. The results obtained are directly supply chain management and competitive advantage have a significant and positive effect on SME's performance. Indirectly supply chain management has a significant and positive effect on SME's performance mediated by competitive advantage. Keywords: supply chain management, SME’s performance, competitive advantage